Ib-M Aisyiyah Group of Tasikmalaya City In Early Detection of Cardiovascular Disease Risk Factors - Ida Rosidawati; Hana Ariyani; Yuyun Solihatin; Bayu Brahmantia; Sunanih Sunanih (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Non-communicable diseases are the largest cause of death in the world, one of which is cardiovascular disease. Health development goals are directed towards achieving an independent society for healthy living, therefore community empowerment is needed to support these goals. This condition is a shared responsibility, especially Muhammadiyah and Aisyiyah Universities as women's organizations that pay attention to health services to the community. The solution offered is the implementation of health services on an ongoing basis whose activities include cadre training, health counselling and blood pressure checks, body mass index and first aid in emergency cardiac disease. The activity was held in 2021; the target was women’s majelis taklim group organized by the Head of Aisyiyah District of Tasikmalaya City. The implementation of activities is carried out by lecturers and students and assisted by PDA Kota Tasikmalaya.